THE FUNCTIONAL RELATIONSHIP OF ISLAMIC EDUCATION PHILOSOPHY WITH SCIENCE AND RELIGION - Suhari Suhari; Iyad Abdallah Al- Shreifeen; Suhana Sarkawi (Adisam Publisher, 2024)
This article discusses the functional relationship of Islamic Education philosophy with science and religion. The relationship between the three is united by a common goal, namely the search for truth. However, even though they are the same, they are also different. The differences lie in the aspects of sources, methods and results that will be achieved by the three so that they will lead to the truth.